2009
DOI: 10.1111/j.1365-2648.2009.05142.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and fluid compliance: an educational intervention for patients having haemodialysis

Abstract: Nurses should emphasize sodium compliance in patients having haemodialysis and explain its adverse effects, such as excessive weight gain, hypertension, and peripheral oedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(109 citation statements)
references
References 25 publications
5
98
0
6
Order By: Relevance
“…Similar are the results of Hain et al [20] and Murray [21] regarding age. Opposite are the results in the study of Baraz et al [22]in which young patients were found more compliant than older after an educational intervention.…”
Section: Demographic Characteristicssupporting
confidence: 90%
See 1 more Smart Citation
“…Similar are the results of Hain et al [20] and Murray [21] regarding age. Opposite are the results in the study of Baraz et al [22]in which young patients were found more compliant than older after an educational intervention.…”
Section: Demographic Characteristicssupporting
confidence: 90%
“…Some of them are age [4,6,7,[19][20][21][22]26,27,28,36] , race [4,6,7,19,23] , sex [4,7,22,26,27] , educational level [6,22,23] , work [27,34],marital status [18,33,34,36]. Studies that have analyzed the demographic characteristics and correlated them with adherence in HD are summarized below (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Baraz et al (2014) also investigated the effect of education on biochemical parameters of 63 patients under hemodialysis in 2 groups of oral and visual educations. In this study, oral education led to a significant decrease in creatinine, phosphate, uric acid, and blood urea nitrogen, but no significant effect was found in other parameters such as albumen, calcium, and potassium (23). In another quasi-experimental study, the effect of intervention based on a self-care model on 32 patients under hemodialysis was investigated.…”
Section: Sufficientmentioning
confidence: 76%
“…Studies also found favorable clinical results and knowledge of nutrition education in hemodialysis patients. In these studies, nutrition education had positive effects on certain biochemical parameters and no significant impact on some others (7,12,(22)(23)(24).…”
Section: Introductionmentioning
confidence: 89%
“…Increased knowledge, better understanding of their disease process and active participation in health behaviors, including dietary restrictions, have been suggested as methods to improve HD adherence and phosphorus control (Baraz, Parvardeh, Mohammadi & Broumand , 2009;Cupisti, et al, 2012;Brogdon 2013;Reddy et al, 2009) …”
Section: Background and Significancementioning
confidence: 99%